2017
DOI: 10.1021/acs.iecr.6b05053
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Adsorption Desulfurization Performance over Mesoporous ZSM-5 by Alkali Treatment

Abstract: The adsorption sulfur capacity and selectivity are two key challenges for adsorption desulfurization technology of FCC gasoline. In order to improve the above issues, the mesopores were first introduced into ZSM-5 zeolites by a NaOH alkali treatment method to reduce the diffusion limitations and increase the sulfur capacity, in which the effects of the alkali concentration, treatment time, and temperature on the pore properties of zeolites were well discussed. The desulfurization performance was tested in a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…For making up the disadvantages of HDS technique, some non‐hydrodesulfurization techniques ( e. g. in situ sulfur removal, reactive adsorption desulfurization, oxidative desulfurization (ODS), alkylation desulfurization and selective adsorption desulfurization (SADS) are being developed as auxiliary methods. Among these technologies, SADS process is regarded as a promising “zero‐sulfur” technology owing to its mild conditions, good desulfurization performance, low cost, and minimal octane loss . So far, various types of adsorbents for SADS have been reported .…”
Section: Introductionmentioning
confidence: 99%
“…For making up the disadvantages of HDS technique, some non‐hydrodesulfurization techniques ( e. g. in situ sulfur removal, reactive adsorption desulfurization, oxidative desulfurization (ODS), alkylation desulfurization and selective adsorption desulfurization (SADS) are being developed as auxiliary methods. Among these technologies, SADS process is regarded as a promising “zero‐sulfur” technology owing to its mild conditions, good desulfurization performance, low cost, and minimal octane loss . So far, various types of adsorbents for SADS have been reported .…”
Section: Introductionmentioning
confidence: 99%
“…Many publications discussed the mechanism of RADS over Ni/ZnO-based adsorbent [8][9][10][11][12][13]. Babich and Moulijin [14] first proposed a mechanism of RADS over Ni/ZnO-based adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…The XRD abbreviation has not been defined before patterns of supported HZSM‐5 are shown in Figure . The XRD patterns of 2.3%MgO/HZSM‐5 and 2.3%CaO/HZSM‐5 had a typical peaks of HZSM‐5 . It was confirmed that the total crystallinity did not change, and the zeolite framework was not broken after loading MgO and CaO.…”
Section: Resultsmentioning
confidence: 75%